GANTI RUGI ATAS PENGADAAN TANAH BAGI PELAKSANAAN PEMBANGUNAN PASAR TRADISIONAL UNTUK KEPENTINGAN UMUM DI KABUPATEN ACEH TAMIANG - MUHAMMAD RACHMAWAN (PREMISE LAW JURNAL, 2017)
One of the government's methods to carry out land acquisition for public interest is by issuing Law No. 2/2012 on Land Acquisition for Public Interest and its Administrative Regulation (PP No. 71/2012). Its implementation has to be done by performing negotiation and reasonable price for the land owner by sticking to the principle of justice so that his economic condition will be better. The result of the research showed that land acquisition for the construction for public interest in small scale is regulated in Law No. 2/2012 in conjunction with PP No. 71/2012 as it has been amended four times and the last one is PP No. 148/2015 which states that the land acquisition for the construction for public interest in small scale is started by with the area from one hectare until five hectares. Its procedure begins with establishing land acquisition committee, determining permit for location, and determining land price with SK No. 1230/KAT/1/2013, SK No. 325/IKA/VI/2013, andSKNo. 492/160/2013 respectively on June 3, 2013. The obstacles faced by the Aceh Tamiang District Administration in implementing land acquisition for the construction of traditional market is the lack of socialization about the implementation of the project and the low price proposed by the Land Acquisition Committee for the construction of traditional market in Aceh Tamiang Regency.